The Evolution of Approaches to Education throughout History: A Historical Analysis of Educational Approaches and Their Evolution (Journal of Advances and Scholarly Researches in Allied Education, 2014)
We presented an evolutionary study of the educational resource structure in our paper, namely of recoverable capital in educational practices from the first phase of human society's history to modernism and modernism. With the historical context as an empirical criterion, the analysis proposes the taxonomy of the means of education - based on the historical criterion - as a personal contribution. In this study, we suggest a general overview of the early past, called the prehistoric period, in which we will concentrate on the first means of education in relation to the incipient educational practices carried out by human societies.